Turkmenistan : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper reviews economic developments in Turkmenistan during 1996-99. Inflation is an issue in Turkmenistan. The trend decline that started in mid-1996 came to a halt in late 1998 and inflation continued to increase in 1999. By mid-1999, 12-month inflation had increased to 25 percent. Owing to payment problems, gas exports to Ukraine were discontinued in early 1997, resulting in a sharp decline in real GDP in that year. In 1998, gas exports did not resume, other than small deliveries to Iran through a new pipeline that had become operational at end-1997.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet